Bcr-Abl1 Transcript Variants in Chronic Myeloid Leukemia Patients: Relationship with Routine Hematological Parameters - Sela, Grace; Aman, Adi Koesoema; Nasution, Malayana R. (Sarana Ilmu Indonesia (Salnesia), 2025)
Chronic myeloid leukemia (CML) was a myeloproliferative neoplasm characterized by the Philadelphia chromosome resulting from the BCR-ABL1 translocation. The most common BCR-ABL1 transcript variants were b2a2 and b3a2, which encoded the p210 protein with increased tyrosine kinase activity. This study was an analytical observational study with a cross-sectional design using retrospective data obtained from medical records. The study analyzed the relationship between BCR-ABL1 transcript variants and routine hematological parameters (hemoglobin, leukocyte count, and platelet count) among CML patients at Adam Malik General Hospital from 2020 to 2024 using a total sampling method. A total of 38 patients met the inclusion criteria, of whom 71,1% had the b3a2 variant and 28,9% had the b2a2 variant. Males predominated (60,5%), with a mean age of 28,37 ± 16,23 years. Leukocyte counts were significantly lower in patients with the b3a2 variant than in those with the b2a2 variant (p = 0,045), whereas hemoglobin and platelet levels showed no significant differences. A statistically significant relationship was found between leukocyte count and BCR-ABL1 transcript variants, while no significant relationship was observed between hemoglobin or platelet levels and transcript variants. The study highlighted the potential association between BCR-ABL1 transcript variants and leukocyte count in CML patients.